Gestão intercultural: a experiência de executivos brasileiros no México - Saravia, João Henrique Gamond (2010)
The main purpose of this work is to identify what are the difficulties that Brazilian executives, characterized by a Brazilian managerial style, deal with when working or doing business in Mexico. We chose Brazil and Mexico because of two main reasons: first because both countries together stand for 60% of Latin America’s GDP. Second, is our personal interest, based on our own work experience with Mexico, that began in 2002 (and still goes on until this present date) when we started to interact with Mexico in our work on a daily basis. In order to reach the purpose of this work we started defining what culture and national culture are, and how they affect the managerial style. We also studied theory on Brazilian and Mexican managerial style, and, once we believe that the managerial difficulties found by those executives might be related to differences in managerial styles, we used Hofstede’s model to compare both styles and identify those differences. Afterwards, we did field research, performing semi-structured interviews with Brazilian managers that worked in Mexico. Those interviews were intended to confirm differences between both styles and identify difficulties that arouse because of them. Finally, we present those differences and conclude that, even though managerial styles in both countries are alike – and that reflects on their similar rankings on all four Hoftede’s dimensions – the differences do bring difficulties that must be taken care of to enable easier adaptation and success on professional challenges that Brazilian executives may endeavor in Mexico.